Genotypically Identifying Wheat Mesophyll Conductance Regulation under Progressive Drought Stress - Olsovska, Katarina; Kovar, Marek; Brestic, Marian; Zivcak, Marek; Slamka, Pavol; Shao, Hong Bo (Frontiers in Plant Science, 2016)
Abstract Photosynthesis limitation by CO2 flow constraints from sub-stomatal cavities to carboxylation sites in chloroplasts under drought stress conditions is, at least in some plant species or crops not fully understood, yet. Leaf mesophyll conductance for CO2 (gm) may considerably affect both photosynthesis and water use efficiency in plants under drought conditions. The aim of our study was to detect the responses of gm in leaves of four winter wheat (Triticum aestivum L.) genotypes from different origins under long-term progressive drought. Based on the measurement of gas-exchange parameters the variability of genotypic responses was analyzed at stomatal (stomata closure) and non-stomatal (diffusional and biochemical) limits of net CO2 assimilation rate (AN). In general, progressive drought caused an increasing leaf diffusion resistance against CO2 flow leading to the decrease of AN, gm and stomatal conductance (gs), respectively. Reduction of gm also led to inhibition of carboxylation efficiency (Vcmax). On the basis of achieved results a strong positive relationship between gm and gs was found out indicating a co-regulation and mutual independence of the relationship under the drought conditions. In severely stressed plants, the stomatal limitation of the CO2 assimilation rate was progressively increased, but to a less extent in comparison to gm, while a non-stomatal limitation became more dominant due to the prolonged drought. Mesophyll conductance (gm) seems to be a suitable mechanism and parameter for selection of improved diffusional properties and photosynthetic carbon assimilation in C3 plants, thus explaining their better photosynthetic performance at a whole plant level during periods of drought.